Monetary Policy and Wealth Effects: The Role of Risk and Heterogeneity - Nicolas Caramp; Dejanir H. Silva (University of California, Department of Economics, 2021)
We study the role of wealth effects, i.e. the revaluation of stocks, bonds, and human wealth, in the monetary policy transmission mechanism. The analysis of wealth effects requires to incorporate realistic asset-pricing dynamics and heterogeneous households' portfolios. Thus, we build an analytical heterogeneous-agents model with two main ingredients: i) rare disasters and ii) positive private debt. The model captures time-varying risk premia and precautionary savings in a linearized setting that nests the textbook New Keynesian model. Quantitatively, the model matches the empirical response of asset prices as well as the heterogeneous impact on borrowers and savers. We find that wealth effects induced by time-varying risk and private debt account for the bulk of the output response to monetary policy.
Keywords: E21; E52; E44; 330; Monetary Policy; Wealth Effects; Asset Prices; Heterogeneity